The effects of spent garnet in high strength concrete subjected to elevated temperature - Khiyon, Mohammad Iqbal (2018)
The ability of garnet to be recycled makes garnet suitable for many industrial purposes. When the recycled garnet can no longer be reused in the ship cleaning process, garnet is removed from the shipyards and named as “spent garnet”. This has resulted in millions of tons of spent garnet disposed in landfill, quarries, oceans and rivers, thus causing environmental problems. The rapid growth of construction industry has leading to the over exploitation of riverbeds. This scenario affects the environment which includes reduction of water quality and destabilization of the stream bed and banks. In this study the spent garnet was used as sand replacement in high strength concrete production. Several laboratory tests were done to determine the characteristics of spent garnet in terms of physical and chemical properties. Trial mix design and evaluation on fresh and hardened properties of high strength concrete were examined to achieve concrete strength 60 MPa at 28 days. Series of the concrete were prepared with a replacement of 0%, 20%, 40%, 60%, 80% and 100% by using spent garnet as a sand replacement with a water cement ratio of 0.33 and 0.33% of superplasticizer from the weight of cement was added to get the desired slump 60-180 mm. Workability of the concrete was studied in addition to hardened properties and durability of the concrete at ambient and elevated temperature. Furthermore, microstructural test which is Scanning Electron Microscopy (SEM) also was done in this research. Finally, the effect of concrete cover when exposed to elevated temperature and the bonding effect between concrete and steel at ambient temperature was determined. Results showed that at 20% and 40% replacement, the compressive strength of the concrete at 28 days were 62.55 MPa and 63.91 MPa, respectively, which is 3.8% and 6% higher than high strength concrete (HSC). High strength concrete mix consisting of 40% spent garnet using different concrete cover thickness subjected to elevated temperature and bonding effect with steel was investigated. From the fire test, 40% of spent garnet gives slightly better protection for steel bar when exposed to elevated temperature compared to HSC. For pull-out test, the results shows that using 40% of spent garnet gives higher bond strength compared to HSC. The failure mode for 50 mm concrete cover shows pull-out failure while 20 and 37.5 mm concrete cover shows splitting failure. Considering the test results, 40% of spent garnet as sand replacement in high strength concrete showed excellent performance in term of strength of concrete subjected to fire.